Efikasi Cendawan Entomopatogen Sebagai Agens Hayati Dalam Mengendalikan Spodoptera frugiperda J.E Smith (Lepidoptera: Noctuide) - Aulia, Rizki; Wilyus, Wilyus; Hayati, Islah (Jurnal Media Pertanian, 2025)
This study was conducted to determine the ability of entomopathogenic fungi as biological agents in controlling Spodoptera frugiperda J.E. Smith. The study was conducted at the Laboratory of Plant Pests and Diseases, Faculty of Agriculture, University of Jambi. Pathogenicity tests were conducted on six types of fungi (Beauveria bassiana from four different sources, Lecanicillium lecanii, Metarhizium anisopliae, and Trichoderma harzianum) and controls for three stages of S. frugiperda (eggs, 3rd instar larvae, pupae) using the dip inoculation method. Efficacy tests were conducted on B. bassiana (Jatisari isolation) using the dip method, including variations in spore concentration (10⁶-10⁹ conidia/ml) and dual application (on eggs and larvae). The variables observed included the incubation period, infection symptoms, mortality, and survival of S. frugiperda at each stage. B. bassiana (Jatisari isolate) showed the highest efficacy on larvae (mortality up to 84% at a concentration of 10⁹ conidia/ml), increasing with increasing spore concentration and multiple applications. Although the effect on adults was not significant, the reduction in larval population showed the potential of B. bassiana as an effective biological agent for controlling S. frugiperda.